Investigation of hard x-ray emissions from terawatt laser-irradiated foils at the Matter in Extreme Conditions instrument of the Linac Coherent Light Source. (1st April 2022) - Fletcher, L.B.; Curry, C.B.; Gauthier, M.; Glenn, G.D.; Chen, Z.; Cunningham, E.; Descamps, A.; Frost, M.; Galtier, E.C.; Heimann, P.; Kim, J.B.; Mo, M.; et al.
Abstract: In this technical report, we investigate the hard x-ray background produced at the Matter in Extreme Conditions (MEC) instrument of the Linac Coherent Light Source (LCLS) from the interaction of a high-intensity (∼10 19 W/cm 2 ) femtosecond laser with solid μm-thick aluminum and polypropylene targets. This background is dominated by bremsstrahlung from laser-generated relativistic electrons, and a measurement of the broadband x-ray spectrum via differential x-ray energy filtering was used to infer the existence of two electron distributions with electron temperatures of Thot = 500 ± 300 keV and Tcold = 5.0 ± 0.5 keV. Simultaneous single-shot measurements of the proton energies accelerated from laser-irradiated solid targets could be correlated with these measurements to further constrain the on-target laser parameters. Measurements of the hard x-ray photon background generated from laser-irradiated foils can be used to directly monitor and test the signal-to-background limits of silicon-based hybrid pixel array x-ray detectors at laser intensities approaching 10 19 W/cm 2 .